Implementation of INLISLITE 3.1 in Processing Printed Book Materials at SMAN 1 Kalanganyar Library - Katrin Setio Devi; Yanti Rohmayanti (Alexandria: Journal of Library and Information Science, 2024)
This research aims to provide an overview of the implementation of the INLISLite in processing printed book materials at the library of SMAN 1 Kalanganyar. The INLISLite 3.1 is a library automation system application designed and officially developed by the National Library of the Republic of Indonesia, used to assist in the process of managing library materials. The method used in this research is a descriptive qualitative research method. Utilizing data collection techniques through observations and interviews with two informants consisting of the head librarian and library staff of SMAN 1 Kalanganyar. The implementation of the INLISLite serves as a solution for the SMAN 1 Kalanganyar library in transitioning from conventional to automated processing of printed book materials. Equipped with comprehensive program features, it aids the staff in their library activities. However, the use of the INLISLite 3.1 at SMAN 1 Kalanganyar has not been fully optimized and is still hindered by human resources, resulting in suboptimal data input due to a lack of cataloging expertise.